Analysis of Public Perception Toward Islamic Banks (A Case Study in Air Tiris Village, Kampar District) - Ibrahim, Zafran (CV. Publikasi Indonesia, 2025)
Islamic banking has experienced significant growth in Indonesia, yet public awareness and utilization remain suboptimal, particularly in rural areas. Air Tiris Village, located in Kampar District, has a predominantly Muslim population of approximately 6,873 residents. However, most Muslims in this village still have minimal understanding of Islamic banking principles, products, and services. This study aims to analyze public perception, awareness, and behavioral tendencies toward Islamic banks among residents of Air Tiris Village. A qualitative descriptive approach was employed, with data collected through observation, semi-structured interviews with ten purposively selected respondents representing various occupations, and documentation. Thematic analysis was conducted following Miles and Huberman’s framework of data reduction, data presentation, and conclusion drawing. The results indicate that while 70% of respondents are aware of the existence of Islamic banks, only 50% have utilized Islamic banking products, primarily savings and financing services. Limited knowledge about Islamic banking products, perceived operational complexity, and insufficient educational outreach contribute to a continued preference for conventional banks. Furthermore, 60% of respondents expressed uncertainty regarding the riba-free nature of Islamic banking contracts, reflecting persistent misconceptions. These findings underscore the critical need for enhanced financial literacy programs, targeted community education, and strategic marketing initiatives to improve public understanding and adoption of Islamic banking services in rural, Muslim-majority communities. Implications for policymakers, financial institutions, and religious educators are discussed.